Measuring and managing the work environment of the mid-level provider - the neglected human resource - McAuliffe Eilish; Bowie Cameron; Manafa Ogenna; Maseko Fresier; MacLachlan Malcolm; Hevey David; Normand Charles; Chirwa Maureen (BMC, 2009)
Abstract Background Much has been written in the past decade about the health workforce crisis that is crippling health service delivery in many middle-income and low-income countries. Countries having lost most of their highly qualified health care professionals to migration increasingly rely on mid-level providers as the mainstay for health services delivery. Mid-level providers are health workers who perform tasks conventionally associated with more highly trained and internationally mobile workers. Their training usually has lower entry requirements and is for shorter periods (usually two to four years). Our study aimed to explore a neglected but crucial aspect of human resources for health in Africa: the provision of a work environment that will promote motivation and performance of mid-level providers. This paper explores the work environment of mid-level providers in Malawi, and contributes to the validation of an instrument to measure the work environment of mid-level providers in low-income countries. Methods Three districts were purposively sampled from each of the three geographical regions in Malawi. A total of 34 health facilities from the three districts were included in the study. All staff in each of the facilities were included in the sampling frame. A total of 153 staff members consented to be interviewed. Participants completed measures of perceptions of work environment, burnout and job satisfaction. Findings The Healthcare Provider Work Index, derived through Principal Components Analysis and Rasch Analysis of our modification of an existing questionnaire, constituted four subscales, measuring: (1) levels of staffing and resources; (2) management support; (3) workplace relationships; and (4) control over practice. Multivariate analysis indicated that scores on the Work Index significantly predicted key variables concerning motivation and attrition such as emotional exhaustion, job satisfaction, satisfaction with the profession and plans to leave the current post within 12 months. Additionally, the findings show that mid-level medical staff (i.e. clinical officers and medical assistants) are significantly less satisfied than mid-level nurses (i.e. enrolled nurses) with their work environments, particularly their workplace relationships. They also experience significantly greater levels of dissatisfaction with their jobs and with their profession. Conclusion The Healthcare Provider Work Index identifies factors salient to improving job satisfaction and work performance among mid-level cadres in resource-poor settings. The extent to which these results can be generalized beyond the current sample must be established. The poor motivational environment in which clinical officers and medical assistants work in comparison to that of nurses is of concern, as these staff members are increasingly being asked to take on leadership roles and greater levels of clinical responsibility. More research on mid-level providers is needed, as they are the mainstay of health service delivery in many low-income countries. This paper contributes to a methodology for exploring the work environment of mid-level providers in low-income countries and identifies several areas needing further research.